2010
DOI: 10.1007/s00417-010-1389-7
|View full text |Cite
|
Sign up to set email alerts
|

Safety and feasibility of a novel intravitreal tamponade using a silicone oil/acetyl-salicylic acid suspension for proliferative vitreoretinopathy: first results of the Austrian Clinical Multicenter Study

Abstract: Aspirin delivery by intravitreal silicone oil in the human eye is safe and also may provide a delivery vehicle for other antiproliferative agents to the posterior pole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
0
16
0
1
Order By: Relevance
“…50 A novel randomized control trial studied the use of standard SO tamponade compared to SO containing aspirin, given aspirin's anti-inflammatory properties. 51 Although no adverse effects were observed with administration of SO containing aspirin, no significant differences were observed either in visual acuity or detachment rates at 6-month follow-up. It would be interesting to repeat this study with aspirin dosing adjustments to investigate if a varying concentration would prove beneficial.…”
Section: Surgerymentioning
confidence: 83%
“…50 A novel randomized control trial studied the use of standard SO tamponade compared to SO containing aspirin, given aspirin's anti-inflammatory properties. 51 Although no adverse effects were observed with administration of SO containing aspirin, no significant differences were observed either in visual acuity or detachment rates at 6-month follow-up. It would be interesting to repeat this study with aspirin dosing adjustments to investigate if a varying concentration would prove beneficial.…”
Section: Surgerymentioning
confidence: 83%
“…Some authors simply do not use any, preferring generic terms, such as minimal, moderate, and severe PVR [ 21 , 22 ]. Furthermore, early stages of PVR (named as grades A and B), which are common to all classifications, are not used, and most authors refer only to most advanced stages, basically grade C [ 20 , 23 ]. Moreover, the presence of classification errors could indicate that there is confusion concerning their use [ 13 , 16 – 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…An important relevant finding is that only a limited number of clinicians appropriately and fully use the current updated classification of 1991 [ 24 27 ], while the majority of authors avoid using the added characteristics of localization, extension, and type, limiting the description to the grade. In addition, many colleagues still use the first reported classification [ 4 ], probably because although it presents many limitations, it is easier to use compared to the last version [ 23 , 28 ]. Additionally, some authors decided to use alternative classification, probably to avoid problems evaluating PVR stages [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies using acetylsalicylic acid reported relatively high drug loading in 5000 mPa.s SO (1.67 mg/ml), although filtration to remove undissolved drug was not performed (Kralinger et al 2001a; Kralinger et al 2001b). In a subsequent clinical trial, the acetylsalicylic acid–SO solution was filtered to remove undissolved drug crystals and resulting in significantly lower drug loading of 0.2 mg/ml (Kralinger et al 2010). In vitro , a burst release was observed, with concentration reduced after 3 days and the drug metabolite, salicylate, was undetectable after 30 days.…”
Section: Recent Development and Innovation Of Somentioning
confidence: 99%